DEVELOPMENT OF AUGMENTED REALITY-BASED LEARNING MEDIA IN THE FORM OF CARDS ON ATOMIC STRUCTURE MATERIAL - Wulandari, Sri; Jusniar, Jusniar; Majid, Ahmad Fudhail (UNESA Journal of Chemical Education, 2023)
This development research aims to produce products in the form of augmented reality-based card media on atomic structure material that is valid, practical, and effective. This development adapts the 4D development model which includes Define, Design, Development, and Disseminate. The subjects in this study were 2 material experts, 2 media experts for the validity test, 2 chemistry teachers, and 36 students of class X MIPA 2 for the practicality and effectiveness test. The instruments used for validity are material expert validation sheets and media expert validation sheets. For practicality, namely the learning implementation observation sheet, teacher and student response questionnaires. While for effectiveness with learning outcomes test. The results showed: (1) The validity of the instrument includes the validation sheet of the observation sheet of the implementation of the device, the teacher response questionnaire, and the response of the students used respectively have an average of 3.8 and 3.65. The validity of learning materials and media has an average of 3.6 and 3.6 and the consistency between validators is in a very high category (100%). (2) the practicality of augmented reality-based learning media based on the learning implementation observation sheet, teacher response questionnaire, and student response questionnaire is 97.5%, 92.2%, and 88.3% respectively which is included in the very practical category, (3) augmented reality-based learning media meets the effective criteria (≥85%) based on the learning outcomes test with a class completeness percentage of 88.9%. Based on these data, the augmented reality-based card-shaped media on atomic structure material using the 4D development model can be declared valid, practical, and effective.